Students’ Anxiety and Self-Esteem in English Language Classroom - Nurhayati Nurhayati; Agatha Merlin Bewa Kaha (Departement of Mathematics Education, 2022)
This study aimed to find out the level of students’ anxiety and self-esteem in English language classroom. Also, this study wanted to investigate whether there are any differences between students’ anxiety and self-esteem in English language classroom based on gender. Furthermore, the main purpose of this study was to find out the correlation between students’ anxiety and self-esteem in English language classroom. The questionnaire based on Foreign Language Anxiety and State Self-Esteem Scale was adopted from Natalia (2014). This Study was conducted on the grade seven students who enrolled in the second semester 2022/2023 academic year of SMP Advent UNKLAB Airmadidi. The result ere: (1) students’ anxiety in English language classroom was at moderate level, (2) students’ self-esteem in English language classroom was at moderate level (3) there is a different level in English language classroom based on gender (4) There was significant correlation between students’ anxiety and self-esteem in English language classroom. This study recommended that future researchers may try to conduct a similar study in a different place and grade.